THE DEVELOPMENT OF ARABIC LANGUAGE STUDIES IN MALAYSIA: A BIBLIOMETRIC ANALYSIS - Ku Yaacob, Ku Mohd Syarbaini; Hasbulah, Muhamad Husni; Yasin, Mohammad Dhiya’ul Hafidh Fatah; Yaakob, Mohd Aizul (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the intersection of Arabic language and social media research in the Malaysian context through a bibliometric analysis, aiming to understand the development, distribution, and thematic focus of scholarly publications in this domain. Despite the growing significance of Arabic language education and digital communication platforms in Malaysia, there has been limited comprehensive analysis of the research trends that shape this evolving field. To address this gap, a bibliometric approach was employed, using four targeted keywords “Arabic language,” “social media,” “Malaysia,” and “bibliometric analysis” to retrieve data from the SCOPUS database. The initial dataset, spanning publications up to December 2023, yielded a total of 852 records. Data cleaning and standardization were conducted using OpenRefine to ensure consistency and accuracy, followed by in-depth mapping and network visualization using VOSviewer (version 1.6.15). SCOPUS Analyzer was also utilized to examine publication trends, prolific authors, source journals, country contributions, and citation impact. The analysis revealed a significant increase in publications post 2015, with a concentration of articles in educational and linguistic journals. Keyword co-occurrence mapping indicated strong thematic links between Arabic language learning, digital pedagogy, online discourse, and non-native speakers. Citation analysis identified the most influential articles, while country level collaboration data highlighted Malaysia’s emerging role in Arabic linguistic research in the digital sphere. This study contributes to a clearer understanding of the knowledge structure and intellectual evolution in this niche area, offering valuable insights for educators, policymakers, and future researchers. It demonstrates the importance of bibliometric tools in tracing research trajectories and identifying strategic directions for future inquiry in Arabic language and social media integration within Malaysia.